PRONUNCIATION OF ENGLISH LABIODENTAL BY ACEH ENGLISH TEACHERS: ACOUSTIC PHONETICS - Muhammad Barru Siddiq; Ridwan Hanafiah; Bahagia Tarigan; Wan Anayati (Jurnal Education and Development, 2021)
The aim of this research is to analysethe patterns of frequency and standardization on English pronunciation of labiodental word /f/, /v/based on male and female Acehnese English teachers. The theories are propose by Gilakjani in Cook(2016) and Praat Applicationpre-6.0.33 version were utilized in analysis process.The descriptive qualitative method was applied. The data used in this research were the English pronunciation of the 5 school inLhokseumawe City.The result showed that there were 19 words pronounced by 5 males and 5 femalesinformant’s English teachers were similar to the USA malenative speaker as theinformant 4 to theten words of labiodental speech sounds pronounced.There were 4 pronunciation of labiodental letters found as well. Furthermore, the standard frequency similarly pronounced to the USA femalenative speaker was informant6 and 8 to the 9 words of labiodental speech sounds. There were four similar pronunciation of labiodental letters. Meanwhile, the other informants’ pronunciation frequency number produced is not similar to the UK native speaker frequency numbers.